Relationship between obesity and left ventricular hypertrophy in children - Johnny Rompis; Erling David Kaunang (Paediatrica Indonesiana, 2010)
Background Obesity is a chronic metabolic disorder associated with cardiovascular disease (CVD) increasing morbidity-mortality rates. It is apparent that a variety of adaptations/alterations in cardiac structure and function occurs as excessive adipose tissue accumulates. This leads to a decrease in diastolic compliance, eventually resulting in an increase in left ventricular filling pressure and left ventricular enlargement.Objective To evaluate left ventricular hypertrophy (LVH) amongÂ  obese using electrocardiographic (ECG) criteria.Methods A cross-sectional study was conducted on 74 children aged 10-15 years from February 2009 to October 2009. The subjects were divided into obese and control groups. Physical examination and standard 12 lead electrocardiography (ECG) were done in both groups.Results Of 37 obese children, LVH were featured in 3 subjects, while in control group, only 1 child had LVH (P= 0.304). We found that mean RV6 in obese and control group were 9.8446 (SD 3.5854) and 11.9662 (SD 3.2857), respectively (P=0.005). As an additional findings, we found that birth weight was related to obesity in children.Conclusion There is no relation between obesity and left ventricular using ECG criteria in obese children aged 10-15 years.